Multisensory method in the study of language skills of students with special educational needswith visual impairment: a preliminary concept - Anuar, Faizul Nizar; Nordin, Mohd Norazmi; Ismail, Siti Zairin; Bahadin, Siti Azura; Yusuf, Robe’ah; Mohd Salleh, Masrina Nadia; Krishnan, Vijayaletchumy (Kohat University of Science and Technology, Institute of Information Technology, 2024)
The factor of academic excellence in primary and secondary school is very relevant to the mastery of reading. Furthermore, the ability to read proficiently is an important skill for academic mastery at a higher level, career and everyday life. Unfortunately, reading difficulty is the main challenge for students in primary and secondary schools, especially special education students. Referring to the International Student Assessment Program (PISA) 2009+ test (Malaysia's first participation) introduced by the Organization For Economic Co-operation and Development (OECD) shows that Malaysia's achievement is at an unsatisfactory level as it is in the bottom third group among 74 countries participants. Malaysia is below the international and OECD average performance (Exhibit 3). Pupils who are 15 years old fail to reach the minimum skill level of almost 60% in Mathematics, while 44% in Reading and 43% in Science.